Polyphenol supplementation boosts aerobic endurance in athletes: systematic review - Cao, Gexin; Zuo, Jing; Wu, Baile; Wu, Ying (Frontiers in Physiology, 2024)
In recent years, an increasing trend has been observed in the consumption of specific polyphenols, such as flavonoids and phenolic acids, derived from green tea, berries, and other similar sources. These compounds are believed to alleviate oxidative stress and inflammation resulting from exercise, potentially enhancing athletic performance. This systematic review critically examines the role of polyphenol supplementation in improving aerobic endurance among athletes and individuals with regular exercise habits. The review involved a thorough search of major literature databases, including PubMed, Web of Science, SCOPUS, SPORTDiscus, and Embase, covering re-search up to the year 2023. Out of 491 initially identified articles, 11 met the strict inclusion criteria for this review. These studies specifically focused on the incorporation of polyphenols or polyphenolcontaining complexes in their experimental design, assessing their impact on aerobic endurance. The methodology adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the risk of bias was evaluated using the Cochrane bias risk assessment tool. While this review suggests that polyphenol supplementation might enhance certain aspects of aerobic endurance and promote fat oxidation, it is important to interpret these findings with caution, considering the limited number of studies available.